2019
DOI: 10.1186/s12879-019-4613-z
|View full text |Cite
|
Sign up to set email alerts
|

The 2017–2018 influenza season in Bucharest, Romania: epidemiology and characteristics of hospital admissions for influenza-like illness

Abstract: BackgroundSeasonal influenza causes a considerable burden to healthcare services every year. To better measure the impact of severe influenza cases in Romania, we analyzed active surveillance data collected during the 2017–2018 season from patients admitted for influenza-like illness (ILI) at a tertiary care hospital in Bucharest.MethodsPatients admitted for acute ILI were included if they were resident in the Bucharest-Ilfov region, had been hospitalized for at least 24 h, and had onset of symptoms within 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The overall low vaccination uptake in our study population and in the country precluded us from performing an analysis of vaccine effectiveness for this study site. Also, lineage determination was only performed for a small proportion of B viruses circulating in the third influenza season investigated, which did not allow an exact quantification of the circulation of B/Victoria vs. B/Yamagata strains, but our data, corroborated with other information from field literature, showed that in the 2017/18 season in the Bucharest‐Ilfov region B/Yamagata accounted for 90.4% of all characterized B strains circulating in hospitalized influenza 25 …”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The overall low vaccination uptake in our study population and in the country precluded us from performing an analysis of vaccine effectiveness for this study site. Also, lineage determination was only performed for a small proportion of B viruses circulating in the third influenza season investigated, which did not allow an exact quantification of the circulation of B/Victoria vs. B/Yamagata strains, but our data, corroborated with other information from field literature, showed that in the 2017/18 season in the Bucharest‐Ilfov region B/Yamagata accounted for 90.4% of all characterized B strains circulating in hospitalized influenza 25 …”
Section: Discussionsupporting
confidence: 43%
“…For the 2017/18 season, the predominance of B viruses was evident in our SARI study, accounting for 86.9% of all influenza cases, but the rate was higher than the one reported for ILI‐based surveillance at the national level (66.5%) 24 . In our study, lineage determination was only performed for a small proportion of B viruses circulating during this season (11.3%, 6/53 cases), but based on the results available from a different study concomitantly conducted in our hospital in the 2017/18 season, B/Yamagata appeared to be the main circulating strain in patients of all ages 25 …”
Section: Discussionmentioning
confidence: 99%
“…In our population, we have seen a predominance of pediatric patients among cases of LCI. While this may reflect to a certain extent a real increased circulation of influenza viruses among young children, who are known to be a risk group for influenza, this may also be driven at least in part by an increased addressability of pediatric patients with ILI to tertiary care rather than primary care services in our country, as previously discussed [19,20]. Furthermore, a potential propensity towards managing fever and administering antiviral treatment in children in the hospital rather than as outpatients cannot be ruled out, and this is probably reflected in the rather short 5 days median length of hospitalization in infants and toddlers.…”
Section: Plos Onementioning
confidence: 83%
“…For example, in Romania, there was a completely heterogeneous circulation in the 3 seasons that preceded the one reported in this study: in 2015/16 influenza A/H1 predominated, [7] in 2016/17 influenza A/H3, [8] and in 2017/18 influenza B circulated in more than two-thirds of cases. [ 9 10 ] For this reason, epidemiological surveillance is needed to detect temporal trends and to make informed decisions and projections regarding the upcoming influenza seasons. Under these conditions, laboratory confirmation of influenza, especially through molecular techniques, is important because it guides clinical therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%